Protein relative estimation from leukemia data using variable slope normalization for reverse phase protein arrays - Anis Farihan Mat Raffei, 1988- author; Mohd. Saberi Mohamad, supervisor; Fakulti Sains Komputer dan Sistem Maklumat (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2011)
Project Paper (Sarjana Muda Sains Komputer (Bioinformatik)) - Universiti Teknologi Malaysia, 2011